A study of the population attitude towards rational use of antibiotics - Petravičienė, Zita; Bartašiūnienė, Vida; Židonienė, Eligija (Slauga. Mokslas ir praktika, 2021)
The World Health Organization (WHO) has expressed concern about the threat posed by bacterial resistance to antibiotics. Irresponsible consumption affects the entire ecosystem. Nowadays this has become a problem as their overuse has reached a level where resistance is growing and spreading and new drugs are lacking to meet this challenge [1]. It is not only doctors who have to take responsibility for their unnecessary use, but also each of us – not to engage in self-medication. Alexander Fleming, a British scientist and professor of bacteriology who was the first to discover the antibiotic penicillin, is very important in the history of antibiotics. Until then, doctors did not have effective means to treat infections like gonorrhea, rheumatism, pneumonia. With the discovery of penicillin, the era of antibacterial drugs began. Concerns expressed a few years ago that society may remain unarmed against infections, as before the discovery of antibiotics, are becoming a real threat [2]. The word "rational" is derived from the Latin word rationalis and means reasonable, thoughtful, purposeful, intelligent, clearly understood, based on new scientific methods [3]. The issue of rational use of medicines was first raised at an international conference of the World Health Organization in 1985 in Nairobi. The principles of rational use of medicines say that the patient must receive high-quality, safe and effective medicines when he needs them, taking into account his clinical characteristics, by individual doses, for the appropriate period, at appropriate intervals, only for a certain time, at an affordable price, with the right information [4]. The majority of the participants of the study stated that antibiotics kill bacteria and less than half - that it kills viruses. The study showed that less than half of the population treats themselves without consulting a doctor. The aim of the study is to reveal the attitude of the population towards the rational use of antibiotics.